2008
DOI: 10.1016/j.mseb.2008.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NiCuZn ferrite nanoparticles and microwave absorption characterization

Abstract: This study aimed at the low temperature synthesis of Ni x Cu 0.5−x Zn 0.5 Fe 2 O 4 ferrite nanoparticles using the citrate precursor method and the reflectivity characterization of Radar absorbing materials. The NiCuZn phase obtained at 350 • C by the Rietveld method showed homogeneous nanoparticle formation. The analysis of particle size and the critical diameter of the domains indicated monodomain formation on nanometric scale. Vibrating sample magnetometry showed that adding copper to NiZn ferrite decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…One of the frequently used methods to tune the complex permeability of spinel ferrites is to dope the ferrites with many metallic ions, such as Cu, Zn, Co, Li, Mn, Mg, etc. [33][34][35][36][37][38]. For this purpose, some attempts were made to verify the correlation between the material constants, permittivity (ε r = ε − jε ) and permeability ( r = − j ) and the microwave absorption in the sintered ferrites that contain divalent metal ions [1,[33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…One of the frequently used methods to tune the complex permeability of spinel ferrites is to dope the ferrites with many metallic ions, such as Cu, Zn, Co, Li, Mn, Mg, etc. [33][34][35][36][37][38]. For this purpose, some attempts were made to verify the correlation between the material constants, permittivity (ε r = ε − jε ) and permeability ( r = − j ) and the microwave absorption in the sintered ferrites that contain divalent metal ions [1,[33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al [11] synthesized Ni x Cu 0.5−x Zn 0.5 Fe 2 O 4 ferrite (0.2 ≤ x ≤ 0.4) nano-particles using the citrate precursor method. Vibrating sample magnetometry (VSM) showed that adding copper to NiZn ferrite decreases magnetization saturation and the calcining temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to boost technological headway it is needed the combination of components with proper electric and magnetic properties [2,5,6,7]. However, as to oxide ceramics such as ferrites, the composition, the synthesis parameters and the intrinsic characteristics (magnetic saturation, permeability and magnetic permittivity) are associated with their structural properties [6,8,9,10]. This has become decisive for obtaining high performance technological materials [11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%